Online Positive Attitude Training: Increasing Resilience Amidst Pandemic - Ardhiani, Lusi Nur; Hyoscyamina, Darosy Endah; Karim, Chamilul Hikam Al (Universitas Negeri Semarang, 2021)
The Covid-19 pandemic has a major impact on mental health conditions of humans in general and students in particular. To be able to cope with stressful conditions and other negative emotions during a pandemic, the ability to survive and rise is needed. The ability to adapt positively to stress, crisis, and adversity while remaining healthy is definition of resilience. Therefore, this study aimed to determine whether online positive attitude training in identifying, integrating and actualizing self-potential can increase the level of students’ resilience during this pandemic. The subjects of this study were 50 students from various Universities, 25 students participated as the experimental group and 25 others participated as the control group. Mann Whitney U statistical test was used to compare the resilience of the experimental and control groups during the pre-test and post-test. The results of the Man Whitney U statistical test showed a significance value of p = 0.006 (p 0.05) which indicates that there was a significant difference between resilience scores of the experimental group (mean rank = 31.10) and the control group (mean rank = 19.90). It was concluded that online positive attitude training was able to increase the level of student resilience amidst pandemic. This study shows that online training can actually be an effective method of educating or improving certain skills.